THE FORM AND MEANING OF MOGAMA VERBAL COMMUNICATION AS LOCAL WISDOM IN POST-MARRIAGE TRADITIONAL CEREMONIES ETHNIC BOLAANG MONGONDOW - Lumempouw, Femmy; Sahetapy, Johan; Jeane Wowor, Meity (JURNAL ILMU BUDAYA, 2024)
The Bolaang Mongondow ethnic group has a rich cultural heritage with elaborate rituals and ceremonies. Research on the Forms and Meanings of Mogama Verbal Communication as Local Wisdom at the Traditional Post-Marriage Ceremony of the Bolaang Mongondow Ethnic: aims: (1) To identify and classify the form and meaning of Mogama verbal communication as local wisdom in the form of words, phrases, clauses, sentences, and discourse at the traditional post-marriage ceremony of the Bolaang Mongondow ethnic group; (2) To explain the form and meaning of Mogama verbal communication as local wisdom in the form of words, phrases, clauses, sentences, and discourse, at the traditional post-marriage ceremony of the Bolaang Mongondow ethnic group